Workshop OBS Studio: Meningkatkan Kompetensi Teknologi Remaja dalam Bidang Siaran dan Multimedia di Pontianak - Wahyudi, Hijrah; Mardiyati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This community service initiative conducted an OBS Studio workshop to enhance teenagers' technological competencies in broadcasting and multimedia production. With the rapid growth of digital content creation, many youths in Pontianak lack technical skills to produce quality content. The workshop aimed to: (1) introduce OBS Studio's basic functions, (2) develop practical streaming and recording skills, and (3) foster creativity in multimedia production. Using hands-on training methods, 30 participants learned scene composition, audio-visual configuration, and live streaming techniques through direct practice and mentoring. Results showed significant skill improvement, with participants successfully creating basic broadcasts and expressing interest in content creation. The activity also formed a peer-learning community for ongoing development. This program demonstrates the importance of digital skills training for youth empowerment in the creative economy era.